Absolute IR vibrational band intensities of hexafluoroacetone: Comparison of experiment and anharmonic ab initio calculation using the second-order operator canonical Van Vleck perturbation theory. (September 2018) - Krasnoshchekov, Sergey V.; Laptev, Vladimir B.; Gainullin, Ivan K.
Highlights: Absolute infrared intensities of fourteen fundamental bands of gaseous hexafluoroacetone were determined in the range of 2000–340 cm −1 . A theoretical ab initio anharmonic vibrational spectrum was calculated by means of operator canonical Van Vleck perturbation theory (CVPT). Good correspondence was achieved between experimental and theoretical values of IR frequencies and absolute integral intensities. The ν4, ν7, ν10 and ν15 fundamental bands were reassigned, and three predicted Fermi resonances were identified in experimental spectra. Abstract: Hexafluoroacetone (HFA, OC(CF3 )2 ) is widely utilized in organic synthesis, chemistry of heat resistant polymers and biochemistry. In this work, infrared (IR) spectra of gaseous HFA were recorded in the range 2000–340 cm −1 with a resolution of 1 cm −1 . For the first time, experimental absolute IR intensities of fourteen fundamental bands of HFA were measured and compared with intensities predicted by anharmonic ab initio calculations. Theoretical molecular structures, semi-diagonal quartic potential energy surfaces (PES), and cubic surfaces of dipole moment (DM) components of HFA were calculated using MP2/cc-pVTZ ab initio quantum-mechanical model. In addition, harmonic frequencies were also calculated at MP2/cc-pVQZ level of theory and used for refining the PES. The numerical-analytic implementation of the second-order operator canonical Van Vleck perturbation theory (CVPT2) was employed for predicting anharmonic IR spectra of HFA. The deviation from observations of predicted IR intensities for ten fundamentals (ν1, ν2, ν8, ν13 –ν21 ) was less than 25% on average. The significant difference between ab initio harmonic intensities calculated with MP2/cc-pVTZ and MP2/cc-pVQZ models for some normal modes indicates that an inaccuracy of the quantum-mechanical model is probably the major source of errors in theoretical intensities. An interpretation of the IR experimental spectra and associated literature data for HFA is accomplished; the ν4, ν7, ν10 and ν15 fundamentals were reassigned. Three predicted Fermi resonances were identified in experimental spectra, ν3 /ν5  + ν8, ν17 /ν10  + ν19 and ν20 /ν9  + ν23 . An empirical fit of harmonic frequencies within anharmonic model assisted in a reliable identification of a number of overtones and binary combination tones. The fitted harmonic frequencies were compared with MP2/cc-pVQZ and a simplified complete basis set (CBS) extrapolation. It was found that MP2/cc-pVQZ frequencies were more reliable. The efficiency and convenience of the theoretical model employed and associated techniques for interpretation of complex spectra of HFA are demonstrated.